PENGARUH EMISI KARBON TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Sektor Energi dan Sektor Perindustrian yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Annisa Nur Laily Yuniasari; Endang Kiswara (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of carbon emissions on firm value in the energy and industrial sectors that received PROPER ratings on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The main issues examined are whether carbon emissions, firm size, leverage, and institutional ownership affect firm value, and whether carbon emissions produced in the energy sector comply with Indonesia’s carbon tax framework. This research is adapted from Han et al. (2023) entitled “Firm-Value Effects of Carbon Emissions and Carbon Disclosures: Evidence from Taiwan.” The research method used is panel data regression, utilizing secondary data obtained from annual reports, sustainability reports, and PROPER data from the Ministry of Environment and Forestry. The research sample consists of 13 companies in the energy and industrial sectors that consistently received PROPER ratings during 2021-2023. The results show that only firm size has a positive and significant effect on firm value. Carbon emissions, leverage, and institutional ownership do not show significant effects on firm value. In addition, the data disclosed by energy sector companies is not sufficient to draw conclusions regarding the alignment of carbon emissions with the carbon tax framework in Indonesia. These findings indicate that environmental factors, especially carbon emissions, have not yet become a main consideration for investors in assessing firm value in Indonesia during the research period.